VARIATION OF HONEYBEES FORAGES AS SOURCE OF NECTAR AND POLLEN BASED ON ALTITUDE IN YOGYAKARTA - Agussalim Agussalim; Ali Agus; Nafiatul Umami; I Gede Suparta Budisatria (Buletin Peternakan, 2017)
The latitude will influence plant type that growth, water availability, soil nutrients, temperature, humidity, rainfall, and sunlight, so that  impact on the ability of plant for flowering. This research was aimed to determine the types of honeybees forages as the source of nectar, pollen and the both based on the latitude in Yogyakarta.  The Research has been conducted in District of Cangkringan and Turi Sleman and Patuk Gunungkidul, Yogyakarta. The research used methods directly survey to observe in plantation area, field, and forest. Identification of plant type for produce nectar and pollen was taken one or two samples, then check the availability of nectar and pollen. The data  of type of bee forage were analyzed by descriptive analysis. The results of research showed that the type of bee forage in Cangkringan with latitude of 500 – 900 and > 1000 m asl were 23 plants consisted of coconut, sugarcane, rice, sengon, chili, tomato, bean, banana, corn, cucumber, melinjo, mahogany, walnut, durian, sesbania grandiflora, cocoa, cherry, eggplant, sweet potato, cassava and acacia. The District of Turi with latitude of 500 – 900 and > 1000 m asl were 18 plants consisted of coconut, calliandra, rice, tomato, banana, corn, mahogany, rambutan, durian, mango, papaya, avocado, jackfruit, guava, melinjo, kapok, sweet potato and cocoa. The District of Patuk with latitude of  200 – 700 m asl were 28 plants consisted of cacao, rice, corn, cassava, peanut, soybean, chili, eggplant, melinjo, orange, guava, durian, avocado, mango, rambutan, starfruit, sapodilla, papaya, banana, jackfruit, breadfruit, leucaena, rosewood, acacia, mahogany, albizzia, sweet potato and coconut. The type of bee forage as the source of nectar and pollen in Yogyakarta is varied so is potential for the development beekeeping honeybees.